Expression of TET and 5-HmC in Trophoblast Villi of Women with Normal Pregnancy and with Early Pregnancy Loss - Wu, Ai-hua; Yang, Dong-yu; Liu, Yu-dong; Chen, Xin; Chen, Xu-long; Lu, Shan; Chen, Shi-ling (Current medical science, 2018)
Summary Increasing evidence suggests that epigenetic dysfunction may influence the stability of normal pregnancy. The ten-eleven translocation (TET) family and 5-hydroxymethylcytosine (5-hmC) were found to be linked with epigenetic reprogramming. The present study aimed to examine the expression of the TET family and 5-hmC in the villi of human embryos and compared their expression between normal pregnancy and early pregnancy loss (EPL). Embryonic villi were collected from normal pregnant women (control) experiencing medical abortion and from EPL patients at gestation ages of 6, 7 and 8 weeks. The mRNAs of TET family were analysed using quantitative polymerase chain reaction (qPCR), and TET proteins using Western blotting and immunohistochemical analysis. The MethylFlash™ Kit was used to quantify the absolute amount of 5-methylcytosine (5-mC) and 5-hmC. Our results showed that the expression of the TETs and 5-hmC in the normal villus decreased with increasing gestational age. Immunohistochemistry revealed that the TET proteins were expressed in the cytoplasm of trophoblasts and their expression was the highest in the 6-week tissue samples, which was consistent with the qPCR and Western blot results. The expression of TET1, TET2, and TET3 was lower in the villi in EPL group than in normal pregnancy group ( P <0.05 for all). It was concluded that the TET family and 5-hmC are critical in epigenetic reprogramming of human embryo. The findings also suggest that a deficiency of TETs in the villus might be associated with human EPL.